Perancangan Sistem Informasi Penjualan pada Apotek - Permatasari, Angelina (Bina Nusantara University, 2013)
The purpose of this study is to analyze the problems on the sales system of a pharmacy, to identify the information needs and to design a sales information system that addresses the information needs. The methodologies used are analysis and design. Analysis are conducted to identify the needs of information through observation, interviews, and surveys of the old system. While the design method used is Object Oriented Analysis and Design (OOAD). This study results in an application design of sales information system for the pharmacy to handle the manual sales system. A computerized sales information system is able to solve problems that occur in the old system and procedures at the pharmacy.